E-006 Delayed coil migration following initially successful balloon-assisted coil embolization of a basilar tip cerebral aneurysm: case report and meta-analysis. (22nd July 2018) - Cristiano, B; Hoss, D; Jacobson, J
Abstract : Background: Delayed coil migration is an infrequently reported complication following endovascular treatment of cerebral aneurysms with detachable coils. Here we report on a verified case of delayed coil migration following initially successful balloon-assisted coil embolization of a broad-based aneurysm of the basilar tip. Additionally, we perform a meta-analysis of case reports available in the literature to identify aneurysm morphological characteristics seen in cases of delayed coil migration. Methodology: Systematic review of PubMed database making use of MeSH terms associated with cerebral aneurysms and delayed coil migration and review of published bibliographies. Results: A 71-year-old man presented with subarachnoid hemorrhage and basilar tip aneurysm measuring 2.5–2.8 mm at the neck and 3.2 (AP) × 3.4 (TR) × 3.2 (CC) in maximal dimension. This was successfully treated with balloon assistance using detachable coils (Axium 3D 3 mm × 4 cm framing coil, completion packing percentage 24%). Follow-up imaging obtained during hospitalization verified stable positioning of the coil mass. Routine surveillance angiography obtained at 8 months however showed migration of the coil mass into a posterior cerebral artery cortical branch. The patient was asymptomatic, and the basilar aneurysm was subsequently treated with stent-coiling. Systematic review of the literature revealed 13 similar cases representing a cohort of 14 cases available for analysis. Aneurysm morphology was uniformly broad based, and most cases occurred in aneurysms less than 5 mm in maximal dimension. Framing coil selection and packing percentage were not reported for the majority of cases. The present case is the first reported to our knowledge occurring in the posterior fossa. Conclusions: Ruptured cerebral aneurysms with small broad-based morphology remain among the most difficult lesions to treat endovascularly. In addition to increased rates of intra-procedural rupture among other inherent technical challenges, the Neuro-Endovascularist may consider adding the possibility of delayed coil migration to his or her list of considerations in addressing such lesions and modify their treatment plan accordingly. In the present case selection of a larger framing coil or higher target packing percentage may have been worthwhile considerations in retrospect. Disclosures: B. Cristiano: None. D. Hoss: None. J. Jacobson: None.